Dose calculation accuracy in proximity of a pacemaker: A multicenter study with threecommercial treatment planning systems. (December 2020) - Delana, Anna; Barbareschi, Agnese; Consorti, Rita; Daniela Falco, Maria
Highlights: TPSs comparison in the out of field dose calculation in proximity of a pacemaker (PMK) was performed. TPSs calculation accuracy in proximity of a PMK and in a water-equivalent medium was evaluated and compared. Three commercial TPSs, commissioned for two different linacs, were considered in a multicenter study. Two dosimeters (TLD and MOSFET) were used and uncertainties of measurements were determined. Detailed results for both modulated and unmodulated beams were reported. Abstract: This study compares Treatment Planning System (TPS) out of field dose calculation on a pacemaker (PMK) during external beam radiotherapy treatment. We consider four TPSs (Elekta-Monaco, Oncentra- Masterplan and two Philips-Pinnacle3) commissioned for two linacs (Elekta Sinergy and Varian Clinac) delivering two test beams (a highly modulated one and a square field) and two clinical breast plans. To calculate and measure dose to a PMK we built a Real Water3 phantom with a PMK embedded in it. Measures are performed with thermo-luminescent dosimeters and Mosfet dosimeters. We evaluate differences between TPS calculated values for the dose to the PMK (both point dose and dose-volume histogram parameters) when the PMK is positioned in the first 10 cm outside the radiation fields. TPS calculation accuracy is evaluated comparing such values with measures. Differences in TPS calculations are on average 3.5 cGy Gy -1 for the modulated beam, and always lower than 2 cGy Gy -1 for the square beam. TPS dose calculation depends mostly on the TPS algorithm and model rather than the linac commissioned. TPSs considered show different degrees of calculation accuracy. In the first 4 cm to the field edge three out of four TPSs are in good agreement with measurements in the square beam, but only one keeps the agreement in the modulated beam: the others show over and underestimations up to +20% −40%. The same accuracy is found considering a homogeneous phantom. Our results confirm what reported in previous studies and highlight the impact of TPS commissioning.